(untitled) (Baghdad Science Journal, 2015)
Epithelial ovarian cancer is the leading cause of cancer deaths in women. To date, an effective screening tool for ovarian cancer has not been identified Several clinical and biological factors including serum cancer antigen 125 (CA- 125) have been assessed for prognostic and predictive relevance CA-125 is an epithelial marker derived from coelomic epithelium. It is elevated in 90% of advanced ovarian cancers and in 50% of early ovarian cancers while 20% of ovarian cancers have low or no expression of CA- 125 CA-125 concentrations were measured by Mini Vidas test (VIDAS CA125 II / BIOMERIEUX / France). The median CA-125 levels were significantly higher in the sera of ovarian cancer patients than in those with benign tumors and in healthy controls. However in correlation with stages the results showed that Patients with stage II have highly significant differences in level of serum CA125 compare with stage I in and stage III.CA125 showed low sensitivity to detect stage I carcinoma of the ovary which limits its value as an initial screening tool therefore combining of CA125 with other markers might enable improved early detection of ovarian cancer as compared with use of this marker alone.